SOX2 is a promising predictor of relapse and death in advanced stage high-grade serous ovarian cancer patients with residual disease after debulking surgery. (1st November 2020) - Bååth, Maria; Westbom-Fremer, Sofia; Martin de la Fuente, Laura; Ebbesson, Anna; Davis, Juliette; Malander, Susanne; Måsbäck, Anna; Kannisto, Päivi; Hedenfalk, Ingrid
ABSTRACT: The transcription factor SOX2 is a well-established and important stem cell marker. Its role in cancer biology remains unclear, but it has been proposed to also be a marker of cancer stem cells. We investigated the role of SOX2 protein expression in women with high-grade serous ovarian cancer (HGSOC) to determine its potential prognostic and treatment predictive value. We constructed a tissue microarray of 130 advanced stage HGSOC tumors with an average of 6 cores each, stained for SOX2 protein expression and evaluated survival outcomes. We also treated two HGSOC cell lines with carboplatin and paclitaxel and measured SOX2 expression by RT-PCR and immunoblotting at different doses and time-points. Among patients with non-radical debulking surgery overall and progression-free survival were shorter for patients with SOX2 positive tumors (mean 26 vs . 39 months, log-rank test: p = .0076, and mean 14 vs . 19 months, p = .055, respectively). Knockdown of SOX2 in cell lines did not affect growth inhibition following chemotherapy treatment. Our results show that SOX2 has a strong prognostic potential among HGSOC patients with residual tumor tissue after debulking surgery and suggest that SOX2 expressing cells remaining after non-radical debulking surgery may constitute a subpopulation of cancer stem cells with greater tumor-initiating potential.